If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6.7 + -6X = -0.1 Solving -6.7 + -6X = -0.1 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '6.7' to each side of the equation. -6.7 + 6.7 + -6X = -0.1 + 6.7 Combine like terms: -6.7 + 6.7 = 0.0 0.0 + -6X = -0.1 + 6.7 -6X = -0.1 + 6.7 Combine like terms: -0.1 + 6.7 = 6.6 -6X = 6.6 Divide each side by '-6'. X = -1.1 Simplifying X = -1.1
| 12+x=4+2x | | 5x+40f(x)x=-5 | | 6x^2=12x-9 | | Cos(4x-10)=0 | | 7x-5y=-68 | | H=-5t^2+7t-4 | | 1x+4y=120 | | 1x+4y=11120 | | 2-2v=v+64 | | x-11=90 | | 3x+y-z=1 | | 0.9375=x+0.25(3) | | 6x-2y-z=-14 | | f(x)=13x+52 | | 2lgx=2 | | (n+5)(p-14)=1400 | | 6y+2z=a+3y | | 2x+3y+z=1 | | 6y+2z=a+3fory | | 0=-5x^3+25x^3-17x | | 4x+3y=330 | | 10-5x=3x+6 | | -3(4p+4)-2(6-11p)=3(8+3p) | | 29+0.25p=59 | | 0.3x+0.4=0.28x+1.16 | | lny=7 | | 0.011x^3+22x-203=0 | | 14=2.50+2.30(m-1) | | E=f-g | | 2=18*3g | | 2(1-3x)=12 | | 3x+30+2x=360 |